Mode of Foreign Entry, Technology Transfer, and Foreign Direct Investment Policy - Mattoo, Aaditya; Olarreaga, Marcelo; Saggi, Kamal (World Bank, Washington, DC, 2014)
Foreign direct investment can take place through the direct entry of foreign firms or the acquisition of existing domestic firms. Mattoo, Olarreaga, and Saggi examine the preferences of a foreign firm and the host country government with respect to these two modes of foreign direct investment in the presence of costly technology transfer. The tradeoff between technology transfer and market competition emerges as a key determinant of preferences. The authors identify the circumstances in which the choices of the government and the foreign firm diverge-and in which domestic welfare can be improved by restrictions on foreign direct investment that induce the foreign firm to choose the socially preferred mode of entry.